Peran Media Sosial Facebook Dalam Pembentukan Opini Publik Terhadap Perdagangan Satwa Liar Ilegal Di Indonesia - Ednanda Belva Aria (STISIPOL Raja Haji, 2025)
Abstract Illegal wildlife trade has become an issue that threatens biodiversity and animal welfare in Indonesia. This activity not only harms the environment but also has the potential to disrupt the overall balance of ecosystems. As one of the most widely used social media platforms in Indonesia, Facebook has great potential in shaping public opinion and raising public awareness on various issues, including this one. This study aims to analyze the role of Facebook in influencing public opinion regarding the illegal wildlife trade. The study uses a case study method. Data for this study was collected through observation, content analysis, and interviews with several Facebook users in Indonesia. Data analysis was carried out using a thematic approach. The findings of this study indicate that the role of Facebook in shaping public opinion regarding the illegal wildlife trade in Indonesia has not been effectively carried out. While Facebook posts can present informative visual evidence and facts, audience responses tend to be passive, limited to likes or shares without substantial discussion or comments. Recommendations from this study suggest that there is a need to improve the strategy for disseminating information regarding the wildlife trade in Indonesia, both from society and the government, so that the message about illegal wildlife trade can reach a wider public and encourage more active engagement.